2019
DOI: 10.3390/cryst9050241
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric Relaxor and Conductivity Mechanism in Fe-Substituted PMN-32PT Ferroelectric Crystal

Abstract: Fe-substituted PMN-32PT relaxor ferroelectric crystals were grown by a high-temperature flux method. The effects of charged defects on the dielectric relaxor and conductivity mechanism were discussed in detail. The Fe-substituted PMN-32PT crystal showed a high coercive field (Ec = 765 V/mm), due to domain wall-pinning, induced by charged defect dipoles. Three dielectric anomaly peaks were observed, and the two dielectric relaxation peaks at low temperature were associated with the diffusion phase transition, w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 31 publications
0
2
0
Order By: Relevance
“…These broad peaks shift towards higher temperatures with increasing frequency of the measurement field. This phenomenon may be associated with the imposition of a number of factors, for instance, as a result of relaxation processes as well as an increase in electrical conductivity in composite samples at high temperatures [36,37,38,39,40].…”
Section: Resultsmentioning
confidence: 99%
“…These broad peaks shift towards higher temperatures with increasing frequency of the measurement field. This phenomenon may be associated with the imposition of a number of factors, for instance, as a result of relaxation processes as well as an increase in electrical conductivity in composite samples at high temperatures [36,37,38,39,40].…”
Section: Resultsmentioning
confidence: 99%
“…It is found that such segregation differently influences the electrical properties of the investigated system. While the electrical properties along the axial direction strongly depend on the PbTiO 3 content, the electrical properties along the radial direction are mainly determined by the ratio of Nb and Mg. Another technological route is presented by Li et al [5]. The authors investigated dielectric and conductivity mechanisms of Fe-substituted PMN-32PT crystals.…”
mentioning
confidence: 99%